Penguatan Pemahaman Pencegahan dan Penanganan Kekerasan di Perguruan Tinggi melalui Kegiatan Sosialisasi bagi Mahasiswa Universitas Muhammadiyah Gombong - Aditya Maulana Rizqi; Nabila Ciptaning Gusti; Shinta Oliviyana Anggita; Asep Herlan (CV. ALIM'SPUBLISHING, 2026)
Violence in higher education remains a serious issue that may threaten students’ safety, well-being, and the quality of the academic environment. Strengthening students’ understanding of violence prevention and management is therefore essential to support the implementation of a safe and inclusive campus policy. This community service activity aimed to strengthen first-year students’ understanding of the Prevention and Management of Violence in Higher Education (PPKPT) through a socialization program at Universitas Muhammadiyah Gombong. The activity was conducted on 26 January 2026 involving 115 first-semester students using a lecture-based approach followed by interactive discussions. Participants’ understanding was evaluated through pre-test and post-test assessments. The evaluation results showed that the average score increased from 61.4 before the activity to 84.8 after the activity, while the proportion of participants achieving a minimum score of 75 increased from 27.8% to 87.8%. These findings indicate that the socialization program effectively improved students’ understanding of violence prevention, reporting mechanisms, and their role in creating a safe, respectful, and inclusive academic environment. Educational socialization is therefore an effective preventive strategy for supporting the implementation of violence prevention policies in higher education.